2006
DOI: 10.1186/1471-2105-7-243
|View full text |Cite
|
Sign up to set email alerts
|

Chaos game representation for comparison of whole genomes

Abstract: Background: Chaos game representation of genome sequences has been used for visual representation of genome sequence patterns as well as alignment-free comparisons of sequences based on oligonucleotide frequencies. However the potential of this representation for making alignment-based comparisons of whole genome sequences has not been exploited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 12 publications
0
43
0
Order By: Relevance
“…Further studies by Almeida et al (2001) showed that CGR is a generalized Markov chain probability table which can accommodate non-integer orders, and that CGR is a powerful sequence modelling tool because of its computational efficiency and scale-independence (Almeida and Vinga, 2002. Such alignment-free methods have been successfully applied for sequence comparison, phylogeny, detection of horizontal transfers, detection of oligonucleotides of interest, meta-genomic studies (Deschavanne et al, 1999;Pride et al, 2003;Sandberg et al, 2003;Teeling et al, 2004;Chapus et al, 2005;Wang et al, 2005;Dufraigne et al, 2005;Joseph and Sasikumar, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies by Almeida et al (2001) showed that CGR is a generalized Markov chain probability table which can accommodate non-integer orders, and that CGR is a powerful sequence modelling tool because of its computational efficiency and scale-independence (Almeida and Vinga, 2002. Such alignment-free methods have been successfully applied for sequence comparison, phylogeny, detection of horizontal transfers, detection of oligonucleotides of interest, meta-genomic studies (Deschavanne et al, 1999;Pride et al, 2003;Sandberg et al, 2003;Teeling et al, 2004;Chapus et al, 2005;Wang et al, 2005;Dufraigne et al, 2005;Joseph and Sasikumar, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Based on oligonucleotide frequencies, the Chaos Game Representations has been used for visual representation and statistical characterization of genome sequence as well as alignment comparisons and establishment of phylogenetic trees [23], [24], [25], [26]. However, following the evolution of frequencies from the beginning to the end of a given sequence has not been exploited.…”
Section: Overview On Chaos Game Representation (Cgrs)mentioning
confidence: 99%
“…A recent article has examined the use of CGRs to visualize and compare whole genomes [11]. The authors examine the use of CGRs to facilitate alignment between DNA sequences as well as similarities.…”
Section: Cgr Overviewmentioning
confidence: 99%